(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
It is known that the water of Sangzor river together with the wastewater from industrial enterprises, poultry complexes, hospitals, car factories, household utilities in the city of Fallaorol and the mineral fertilizer saturated with mineral fertilizers from the irrigated fields around Fallaorol and household waste water is polluted due to disposal through three collectors (Karabulok, Kichikbulok and SHorbulok)[1-3]. Long-term observations have shown that the salinity of this wastewater flowing into the Sangzor River reaches 2.7-3.2 g|l and the hardness exceeds 20-31 mg.eq|dm3. The amount of chloride, sulfate, phosphate, nitrate and nitrite ions in water is increasing year by year. In particular, the amount of iron in water increased from 0.007 mg|l to 0.35 mg|l and the amount of solid residues (substances that do not settle in water) increased by 1.5-2 times.